Dehumanization and trans-humanization in contemporary American Science Fiction: exploring the possibilities of a unifying vision - Orin, Khandaker Tasnuva (Brac University, 2020)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Masters of Arts in Teaching to Speakers of Other Languages, 2019.